2021
DOI: 10.1159/000518542
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leiomyoma: A Clinical Study of 152 Patients

Abstract: <b><i>Background:</i></b> Cutaneous leiomyoma (CL) is a benign smooth muscle tumour included in painful skin tumours. Multiple CLs are cutaneous markers of hereditary leiomyomatosis and renal cell cancer (HLRCC). <b><i>Objectives:</i></b> To retrospectively review our series of patients with CLs to analyse their clinical features and the association with HLRCC. <b><i>Methods:</i></b> Cases coded as CL in the database of the pathology depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…HLRCC patients with stage III cancer show the worst progression-free survival and overall survival rates [ 8 ]. It has been reported that HLRCC patients were confirmed in 8 of 11 patients with multiple piloleiomyomas (73%) [ 9 ], which was highly frequent. Patients with leiomyomas without HLRCC were older than patients with HLRCC (56 vs. 34 years, p = 0.009) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…HLRCC patients with stage III cancer show the worst progression-free survival and overall survival rates [ 8 ]. It has been reported that HLRCC patients were confirmed in 8 of 11 patients with multiple piloleiomyomas (73%) [ 9 ], which was highly frequent. Patients with leiomyomas without HLRCC were older than patients with HLRCC (56 vs. 34 years, p = 0.009) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HLRCC is estimated at 1 in 200,000 [6], and penetrance is unknown [4]. HLRCC presents dermatologically with non-malignant smooth muscle tumours surrounding hair follicles, called multiple pilar leiomyomas or piloleiomyomas [7]. Piloleiomyomas appear as reddish-brown or flesh-coloured, tender or non-tender firm papules or nodules which may be sensitive to pressure or cold [7].…”
Section: Hereditary Leiomyomatosis and Renal Cell Cancermentioning
confidence: 99%
“…HLRCC presents dermatologically with non-malignant smooth muscle tumours surrounding hair follicles, called multiple pilar leiomyomas or piloleiomyomas [7]. Piloleiomyomas appear as reddish-brown or flesh-coloured, tender or non-tender firm papules or nodules which may be sensitive to pressure or cold [7]. They predominantly occur on the trunk and limbs, along the lines of Blaschko, or adopting linear, segmental or zosteriform patterns [7].…”
Section: Hereditary Leiomyomatosis and Renal Cell Cancermentioning
confidence: 99%
See 2 more Smart Citations